Effect of voltage on electrochemical mechanical polishing (ECMP) of 4H–SiC with fixed abrasives - Pengfei Wu; Dongdong Zhao; Ning Liu; Chao Tang; Jun Li; Yongwei Zhu (Journal of Materials Research and Technology)
This study employs the fixed agglomerated diamond abrasive pad (FADAP) to enhance the processing efficiency and surface quality of 4H–SiC. The effects of voltage on real-time current density, interface resistance, material removal rate (MRR), and surface roughness Ra during the electrochemical mechanical polishing (ECMP) process are investigated, providing both theoretical and experimental insights for process optimization. A fixed abrasive ECMP equipment was developed, and polishing experiments on 4H–SiC were conducted using the slurry composed of 10 % NaNO3 and 7 % H2O2. The variations in real-time current density, interface resistance, MRR, and surface roughness Ra were measured and analyzed within the voltage range of 0–9 V. The results indicate that as the voltage increases, both real-time current density and interface resistance rise, while their growth amplitude gradually declines. When the voltage increased from 0 V to 9 V, the MRR improved from 20.736 μm/h to 25.261 μm/h, representing an approximately 22 % increase compared to the no-voltage condition. Within the experimental range, a linear correlation is observed between current density and MRR, while the surface roughness Ra gradually decreases and stabilizes at approximately 23 nm. By analyzing the effects of voltage on the electronic activation energy of the 4H–SiC surface and the electro-Fenton reaction in the polishing slurry, the mechanism by which voltage enhances MRR in ECMP was elucidated. This study provides systematic theoretical and experimental support for 4H–SiC ECMP, contributing to the optimization of process parameters and the improvement of semiconductor processing quality.